1993
DOI: 10.1007/bf01268094
|View full text |Cite
|
Sign up to set email alerts
|

B-scan ultrasonography in Graves' Orbitopathy

Abstract: Diagnosing and monitoring of Graves' Orbitopathy (GO) can be supported by use of Ultrasonography (USG) and Computerized Tomography (CT); they provide supplementary information. In this retrospective study we describe 107 clinical GO patients evaluated by B-scan USG and 27 clinical GO patients evaluated by CT scan. Analysis of 236 B-scan USG included measurements of medial, inferior and lateral rectus muscles. The presence of muscle enlargement and increased orbital fat were noted by the radiologist on 27 CT sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…Similar to other studies (8,32,33), no correlation was found between CAS and reflectivity or SIR, perhaps because CAS has wide a variation among observers (1,4) or because the great majority of imaging methods assesses only the EOM and not orbital fat inflammation (4,8). We noted that combining the US and MRI resulted in significant increase in the positive predictive value and in specificity.…”
Section: Discussionsupporting
confidence: 70%
“…Similar to other studies (8,32,33), no correlation was found between CAS and reflectivity or SIR, perhaps because CAS has wide a variation among observers (1,4) or because the great majority of imaging methods assesses only the EOM and not orbital fat inflammation (4,8). We noted that combining the US and MRI resulted in significant increase in the positive predictive value and in specificity.…”
Section: Discussionsupporting
confidence: 70%
“…The frequency of the involvement of each muscle was comparable to the findings of three other groups (18)(19)(20), in spite of the exclusion of GO patients with no diplopia from our series. Muscle thickness correlated only weakly with the activity of disease estimated from the T2 relaxation time.…”
Section: Discussionsupporting
confidence: 65%
“…For patient follow-up in Graves' ophthalmopathy, the most widely used imaging methods are sonography, CT, and MR imaging. The accuracy of A-and B-mode sonography is less reliable than CT or MR imaging [9][10][11]. To visualize the muscle belly at its greatest diameter on sonography requires unrestricted free gaze by the patient in several directions during examination, which is usually impossible because of eye muscle dysfunction in these patients.…”
Section: Discussionmentioning
confidence: 99%